FORMULATION, PHYSICAL EVALUATION, AND STABILITY TEST OF CAPSULES FROM A MIX OF EXTRACTS OF Cucurbita moschata Duch AND Sauropus androgynus (L.) Merr. - Yuliastuti, Definingsih; Subarti, Dwi; Pratiwi, Pramita Yuli; Bresky, Eriza; Salsabila, Azra Muthia (Poltekkes Kemenkes Surakarta, 2024)
Pregnant women and postpartum mothers need iron intake and need intake to prepare their breast milk production. Cucurbita moschata Duch. seeds contain essential iron for pregnant women, and Sauropus androgynus (L.) Merr. leaves have active compounds that are effective in increasing breast milk production needed by postpartum mothers. Capsule preparation is used as an alternative preparation development because it is considered easier to consume and practical. This study aims to make capsule preparations that can be used as iron intake by pregnant women and breast milk boosters and evaluate the preparation and the stability of the preparation. This study used an experimental method by making a capsule preparation formula with different talc compositions (F1 (1%), F2 (5%), and F3 (10%)) and conducting physical evaluation including flow properties tests, angles of repose, capsule weight uniformity, capsule disintegration time, and physical stability tests using the cycling test method for 6 cycles and cross-combination at 40°C and 4°C, as well as its microbiological stability. The results showed that the capsule preparations in F1, F2, and F3 had good physical quality. The more talc concentration added, the better the flow speed and angle of repose, and the capsule produced has a uniform weight. The results of the physical stability of Cucurbita moschata Duch. seeds extract capsules and Sauropus androgynus (L.) Merr. leaves meet the requirements of good capsule results from the 1st cycle to the 6th cycle. The storage cycle affects the stability test of capsule water content but does not affect the organoleptic stability test, flow speed, angle of repose, weight uniformity, water content, or microbiology.